Information Lifecycle Governance (ILG): Maximise data value, reduce data growth, cost and risk - Lambrechts, Jan (Journal of Telecommunications and the Digital Economy, 2020)
Over-retention of data with no value leads to increased cost and risk, and reduces the capacity of organisations to identify and leverage valuable business data. Information Lifecycle Governance (ILG) provides a structured, strategic approach to reducing data growth, cost and risk, while providing the policies, processes and technology to move from a reactive to a proactive state of information management and maximise the value of information.